2016
DOI: 10.1007/s11832-016-0769-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of insurance status on ability to return for outpatient management of pediatric supracondylar humerus fractures

Abstract: PurposeOutcomes are excellent following surgical management of displaced supracondylar humerus fractures. Short delays until surgical fixation have been shown to be equivalent to immediate fixation with regards to complications. We hypothesized that insurance coverage may impact access to care and the patient’s ability to return to the operating room for outpatient surgery.MethodsA retrospective review of supracondylar humerus fractures treated at a large urban pediatric hospital from 2008 to 2012 was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
1
20
0
1
Order By: Relevance
“…This study established that Health Insurance was a determinant of orthopaedic services utilisation, similar to studies on Household Health expenditure Surveys noted in the literature review section, and assertions by Fletcher, (2016). Clients without health insurance were 83 percent less likely to use orthopaedic services compared to those with Insurance and this difference was statistically different at p = 0.003.…”
Section: Client Demographic and Social Characteristics Have A Bearingsupporting
confidence: 80%
“…This study established that Health Insurance was a determinant of orthopaedic services utilisation, similar to studies on Household Health expenditure Surveys noted in the literature review section, and assertions by Fletcher, (2016). Clients without health insurance were 83 percent less likely to use orthopaedic services compared to those with Insurance and this difference was statistically different at p = 0.003.…”
Section: Client Demographic and Social Characteristics Have A Bearingsupporting
confidence: 80%
“…This finding is similar to a previous analysis that identified an association between surgery for upper extremity fracture and private insurance [ 29 ]. Additionally, previous analysis of supracondylar humerus fractures treated as outpatients in the pediatric population found that privately insured patients were nearly two and a half times as likely to return for surgical intervention than those with public or no insurance [ 30 ]. This independent association between lower surgical intervention rates and non-private insurance may be a barrier to care that pushes the treating surgeon to admit these patients rather than discharge for outpatient follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This risk has been borne out in previous literature; however, this study further characterized this risk based on timeline. 1 2 3 4 5 6 , 12 , 19 - 21 , 26 , 27 The delay between injury and referral for patients with government-funded insurance was 2.8 times higher than patients with commercial insurance. This delay directly affects the time to orthopaedic evaluation, where the average wait time, for these patients, is almost twice as long at 9.2 days over commercial insurance patients.…”
Section: Discussionmentioning
confidence: 98%
“…Pediatric orthopaedic patients with government-funded health insurance experience longer periods of time before receiving definitive treatment compared with commercially-insured patients at a national level. 1 2 3 4 5 6 , 9 , 19 20 21 22 23 24 The current literature successfully identifies these issuess but has been unable to determine why the issue exists or provide solutions that generate meaningful change. Our study attempts to localize this issue based on the timeline of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation